Effect Of Enzymes, Temperature And Ph On Bacteriocin Activity Of Bacillus Megaterium Against Some Fungal Pathogens (Applied Biological Research, 2018)
The members of genus Bacillus are known to produce a wide range of  antimicrobial substances, including peptide and lipopeptide antibiotics and  bacteriocins that show wide antimicrobial spectra against food-spoilage  microorganisms. The present study was aimed toevaluate the efficacy of  bacteriocins from Bacillus megaterium against some selected spoilage fungi. B.  megaterium was isolated from anise (Pimpinella anisum). The spoilage fungi  were isolated from banana, strawberry, orange, lemon, apple, anion, cucumber,  carrot, turnip and corn. Antifungal activity of extracted bactreriocin was  determined at wide pH range (2-10), storage temperatures (-18, 4, 30 and 45°C  for 15 days) and enzymes treatment (trypsin, pepsin, amylase and lipase) by  agar well diffusion method against nine fungi. Aspergillus niger, Penicillium  digitatum, Penicillium italicum and Fusarium oxysporum were found sensitive to  bacteriocin and showed maximum zone of inhibition (12-16 mm). Partial characterization showed that the bactériocin was a glycolipoprotein, stable at 2-8 pH range, actives at all storage temperatures and was extracted in stationary phase of growth.
Keywords: Anise; Bacillus megaterium; bacteriocin; characterization; spoilage fungi